2020
DOI: 10.4103/ajns.ajns_193_20
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between histopathology of herniated lumbar intervertebral disc and clinical findings

Abstract: Objective: Prolapsed lumbar disc is one of the most frequent diseases, which is usually presented by motor and sensory deficits. Consistency of herniated disc may play a significant role in surgical treatment and postoperative improvement. The objective of this study is to assess whether the histopathological degeneration in the sample of lumbar discs operated on is correlated to clinical variables and surgical outcomes. Materials and Methods: A randomized double-blind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Their study revealed tears or formation of clefts, edge neovascularization and rim lesions, mucoid degeneration, and chondrocyte proliferation as the most frequent alterations in degenerated discs. Ammar et al analyzed disc specimens from 21 patients with disc herniation according to aging-associated pathological disc changes classified previously by Boos et al [ 1 ]. They reported that they found no significant pathological changes in herniated disc specimens, such as increased cartilage cell proliferation and clusters, within the nucleus pulposus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study revealed tears or formation of clefts, edge neovascularization and rim lesions, mucoid degeneration, and chondrocyte proliferation as the most frequent alterations in degenerated discs. Ammar et al analyzed disc specimens from 21 patients with disc herniation according to aging-associated pathological disc changes classified previously by Boos et al [ 1 ]. They reported that they found no significant pathological changes in herniated disc specimens, such as increased cartilage cell proliferation and clusters, within the nucleus pulposus.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of radicular pain is lumbar disc herniation with a lifetime prevalence of about 10% [ 1 ]. One of the most likely causes of this problem is intervertebral disc degeneration and according to some studies, this degeneration is the key alteration that causes low back pain [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, vertebral degenerative diseases are associated with degenerative cartilage endplates [9]. Cartilage cell proliferation and degenerated fibrocartilaginous stroma are often observed in herniated lumbar intervertebral discs [10]. The underlying cervical degeneration from the ACDF presents another potential contributor to the growth of fibrocartilage tissue in the titanium spacers.…”
Section: Discussionmentioning
confidence: 99%
“…LBP also occurs due to psycho-social factors and abnormal biomechanics. Deterioration in the structure of the spine changes the natural environment of the cells of the disc and results in cell-mediated degeneration that causes low back pain [1,2] . About 80% of patients of disc prolapse among the adult population present with LBP [3] .…”
Section: Introductionmentioning
confidence: 99%